2016
DOI: 10.1016/j.jhydrol.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of biochar concentration and particle size on hydraulic conductivity and DOC leaching of biochar–sand mixtures

Abstract: 8The amendment of soil with biochar can sequester carbon and alter hydrologic properties by 9 changing physical and chemical characteristics of soil. To understand the effect of biochar 10 amendment on soil hydrology, we measured the hydraulic conductivity (K) of biochar-sand 11 mixtures as well as dissolved organic carbon in leachate. Specifically, we assessed the effects of 12 biochar concentration and particle size on K and amount of DOC in the soil leachate. To better 13 understand how physical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 49 publications
21
103
0
Order By: Relevance
“…Uzoma et al (2011) concluded that reduction of Ks in sandy soil after application of biochar was a result of increasing water retention capacity. These results together confirm that biochar amendment does influence hydraulic conductivity and the mechanisms that control it are largely physical, including the relative size of biochar and soil particles and their proportions (Liu et al, 2016) and swelling and grain segregation, leading to the clogging of pores, decrease in pore radii, and possibly a variation in bulk density and sample heterogeneity over the experiment (Barnes et al, 2014).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Uzoma et al (2011) concluded that reduction of Ks in sandy soil after application of biochar was a result of increasing water retention capacity. These results together confirm that biochar amendment does influence hydraulic conductivity and the mechanisms that control it are largely physical, including the relative size of biochar and soil particles and their proportions (Liu et al, 2016) and swelling and grain segregation, leading to the clogging of pores, decrease in pore radii, and possibly a variation in bulk density and sample heterogeneity over the experiment (Barnes et al, 2014).…”
Section: Discussionsupporting
confidence: 62%
“…These fine particles can block pores and decrease Ks. Liu et al (2016) found that Ks decreased significantly (by 67%, p<0.01) when biochar particles (<0.251 mm) are smaller than sand particles (0.251-0.853 mm) and decreased by 15% (p<0.01) when biochar particles (0.853-2.00 mm) are bigger than sand particles. When biochar and sand particles sizes are comparable, no significant changes in hydraulic conductivity were observed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As the amount of biochar increased, bulk density decreased linearly (Głąb et al, 2016;Liu et al, 2016a), but in a few cases, it decreased quadratically (Rogovska et al, 2016). The study by Rogovska et al (2016) found that biochar application rates above 60 Mg ha -1 had a smaller effect on reducing bulk density than application rates below 60 Mg ha -1 .…”
Section: Biochar and Compaction Or Mechanical Properties Bulk Densitymentioning
confidence: 95%
“…Soil particle density is 2.6 Mg m -3 regardless of its particle size, while for wood-derived biochar (WBC) with a particle size of less than 70 µm it ranges between 0.6 and 1.6 Mg m -3 , depending on the wood source (Hu et al, 2016;Yargicoglu et al, 2015). Due to the relatively low true density of biochar, its amendment to soils have been reported to decrease soil bulk density (ρ) (Abel et al, 2013;Andrenelli et al, 2016;Bayabil et al, 2015;Castellini et al, 2015;Liu et al, 2016;Obia et al, 2016). For example, Reddy et al (2015) found the specific gravity of silty clay, WBC (particle sizes < 420 µm), and silty clay amended with 5, 10, and 20% WBC to be 2.6, 0.81, 2.1, 2.0, and 1.8, respectively.…”
Section: Introductionmentioning
confidence: 99%